Environment-friendly water-blocking photovoltaic cable and processing technology thereof
By using modified concave and convex rod soil and thiol-containing flame retardant in photovoltaic cables to prepare multi-layer protective structures, the problem of photovoltaic cables being susceptible to moisture intrusion is solved, and efficient flame retardant and waterproof performance is achieved, while ensuring environmental protection.
Patent Information
- Application Number
- CN202510201972.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-24
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-02-24
AI Technical Summary
Existing photovoltaic cables are susceptible to moisture intrusion during use, resulting in degraded insulation performance and electrical failures, and traditional waterproofing agent fluorine-containing compounds are not environmentally friendly.
The water barrier layer is prepared by melt extrusion method using modified concave and convex rod soil, polypropylene, compatibilizer and lubricant, and the surface is coated with protective coatings containing N, Si, S, and P elements, end epoxy polydimethylsiloxane and other materials to form a multi-layer protective structure.
It realizes effective flame retardant and waterproofing at high temperatures, improves the heat resistance and hydrophobic properties of the material, ensures the safety and stability of photovoltaic cables, and avoids environmental pollution.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cables, and in particular to an environmentally friendly water-blocking photovoltaic cable and a processing technology thereof. Background Art
[0002] As people pay more attention to environmental issues, environmentally friendly polypropylene has gradually become a hot spot in cable insulation research and development. Polypropylene has the advantages of low cost, good heat resistance, and plasticization and recycling. However, the flammability of polypropylene limits its application in some applications.
[0003] In addition, an important problem faced by photovoltaic cables during use is water intrusion. The infiltration of water will not only lead to the decline of cable insulation performance, but also may cause electrical faults such as short circuits, seriously affecting the safety and stability of photovoltaic systems. At present, most traditional waterproofing agents on the market use fluorine-containing compounds. Although these materials have good waterproof properties, they are significantly insufficient in terms of environmental friendliness, posing a potential threat to the ecological environment.
[0004] Therefore, we propose an environmentally friendly water-blocking photovoltaic cable and its processing technology. Summary of the invention
[0005] The purpose of the present invention is to provide an environmentally friendly water-blocking photovoltaic cable and a processing technology thereof to solve the problems raised in the prior art.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A processing technology for environmentally friendly water-blocking photovoltaic cables comprises the following steps:
[0008] Step S1: uniformly mixing modified attapulgite, polypropylene, a compatibilizer, and a lubricant, and melt-extruding the mixture to obtain a water-blocking layer;
[0009] Step S2: uniformly mixing the modified attapulgite, the epoxy-terminated polydimethylsiloxane, the waterborne epoxy resin and the curing agent to obtain a protective coating;
[0010] Step S3: sequentially wrapping a water-blocking layer, a shielding layer, and a water-blocking layer on the outer surface of the wire core, coating the surface of the water-blocking layer with a protective coating, and after curing, obtaining a protective layer sleeve to prepare an environmentally friendly water-blocking photovoltaic cable.
[0011] Furthermore, the water-blocking layer is composed of the following components in parts by weight: 50-60 parts of polypropylene, 10-20 parts of modified attapulgite, 1-3 parts of a compatibilizer, and 0.5-1.0 parts of a lubricant.
[0012] Furthermore, the compatibilizer is one of polypropylene grafted with maleic anhydride and maleic anhydride grafted with ethylene-octene copolymer.
[0013] Furthermore, the lubricant is PP wax.
[0014] Furthermore, the protective coating is composed of the following components in parts by weight: 5-10 parts of modified attapulgite, 3-8 parts of epoxy-terminated polydimethylsiloxane, 40-50 parts of water-based epoxy resin, and 8-12 parts of curing agent.
[0015] Further, the preparation method of the modified attapulgite is as follows:
[0016] Step (1): ultrasonically dispersing attapulgite in a mixed solution of ammonia water and propylene glycol methyl ether, adding ethyl orthosilicate, hexadecyltrimethoxysilane, and γ-methacryloxypropyltrimethoxysilane, reacting at 55-65° C. for 2-4 hours, filtering, washing, and drying to obtain attapulgite containing double bonds;
[0017] Step (2): Under nitrogen protection, the mercapto-containing flame retardant and octadecyl mercaptan are mixed evenly to obtain a mixture; the double-bond attapulgite, the mixture and a photoinitiator are mixed evenly, and after irradiation with ultraviolet light, modified attapulgite is obtained.
[0018] In the above technical scheme, attapulgite (ATP), tetraethyl orthosilicate (TEOS), hexadecyltrimethoxysilane (HDTMS) and γ-methacryloxypropyltrimethoxysilane (MPTMS) are used as main raw materials, and attapulgite containing double bonds is prepared by the Stober method; then, the attapulgite containing double bonds is subjected to a thiol-ene click reaction with a thiol-containing flame retardant and octadecyl mercaptan to obtain modified attapulgite.
[0019] Furthermore, in the step (1), the double bond-containing attapulgite is composed of the following components in parts by weight: 15-25 parts of attapulgite, 20-40 parts of aqueous ammonia, 80-100 parts of propylene glycol methyl ether, 15-30 parts of tetraethyl orthosilicate, 5-10 parts of hexadecyltrimethoxysilane, and 8-12 parts of γ-methacryloxypropyltrimethoxysilane.
[0020] Furthermore, in the step (2), the mass ratio of the mercapto-containing flame retardant to octadecyl mercaptan is 1:(0.5-1.0).
[0021] Furthermore, in the step (2), the mass ratio of the double-bond attapulgite, the mixture and the photoinitiator is 1:(1-3):(0.03-0.10).
[0022] Furthermore, the photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone
[0023] Furthermore, the process conditions of the ultraviolet irradiation are: irradiation wavelength 360-400nm, irradiation time 0.5-2.0h, irradiation intensity 25-35mW / cm 2 .
[0024] Further, the preparation method of the mercapto-containing flame retardant is as follows:
[0025] Step A: 1,5-diaminonaphthalene, 3-aminopropyltriethoxysilane and ethanol are uniformly mixed, a mixed solution of terephthalaldehyde and ethanol is added, and the mixture is reacted at 60-70° C. for 4-6 hours to obtain an amino compound;
[0026] Step B: Under nitrogen protection, L-cysteine, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 1-hydroxybenzotriazole are mixed evenly, reacted for 2-3 hours, a mixed solution containing an amino compound and DMF is added dropwise, and the mixture is added dropwise for 30-50 minutes, and the mixture is reacted at 30-40° C. for 6-8 hours. After filtering, washing and drying, an intermediate is obtained;
[0027] Step C: Under nitrogen protection, the intermediate, DOPO and ethanol are mixed evenly, refluxed at 70-80° C. for 10-12 hours, cooled to room temperature, filtered, washed and dried to obtain a thiol-containing flame retardant.
[0028] In the above technical scheme, the amino groups in 1,5-diaminonaphthalene and 3-aminopropyltriethoxysilane are respectively used to undergo Schiff base reaction with the aldehyde groups at both ends of terephthalaldehyde to obtain an amino compound containing a C=N bond; then the carboxyl group in L-cysteine is used to undergo condensation reaction with the amino group in the amino compound to introduce thiol and amino groups to obtain an intermediate; finally, the C=N bond of the intermediate is reacted with the PH bond in DOPO to obtain a flame retardant containing N, Si, S, and P elements, which has excellent flame retardant effect and reaction activity.
[0029] Furthermore, in step A, the mass ratio of 1,5-diaminonaphthalene, 3-aminopropyltriethoxysilane, ethanol and terephthalaldehyde is 1:(1.4-1.6):(8-10):(0.8-0.9).
[0030] Furthermore, in step A, the mass ratio of terephthalaldehyde to ethanol is 1:(2-4).
[0031] Furthermore, in the step B, the mass ratio of L-cysteine, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 1-hydroxybenzotriazole is 1:(0.1-0.2):(0.08-0.10).
[0032] Furthermore, in step B, the mass of the amino compound is 2-2.5 times the mass of L-cysteine, and the mass ratio of the amino compound to DMF is 1:(2-4).
[0033] Furthermore, in step C, the mass ratio of the intermediate, DOPO and ethanol is 1:(1-3):(8-10).
[0034] Furthermore, the wire core is formed by twisting 3-6 tinned copper wire conductors.
[0035] Furthermore, the shielding layer is a copper tape with a thickness of 2-5 mm.
[0036] Furthermore, the coating thickness of the protective coating is 100-200 μm.
[0037] Furthermore, the thickness of the water-blocking layer is 3-5 mm.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] 1. An environmentally friendly water-blocking photovoltaic cable and its processing technology of the present invention use 1,5-diaminonaphthalene, 3-aminopropyltriethoxysilane and terephthalaldehyde as raw materials to obtain an amino-containing compound, and introduce a rigid compound 1,5-diaminonaphthalene with a naphthalene ring to improve its heat resistance; then use a 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) / 1-hydroxybenzotriazole (HOBt) dehydration system to promote the condensation reaction between the carboxyl group in L-cysteine and the amino group in the amino-containing compound, introduce a thiol group and an amino group to obtain an intermediate; finally, the C=N bond of the intermediate reacts with the PH bond in DOPO to obtain a thiol-containing flame retardant containing N, Si, S, and P elements, forming a multi-element synergistic effect, which can release smoke and flame-retardant gases that inhibit combustion at high temperatures, thereby improving the flame retardant effect of the material.
[0040] 2. An environmentally friendly water-blocking photovoltaic cable and a processing technology thereof of the present invention are obtained by grafting double bonds and hydrophobic long carbon chains on the surface of attapulgite to obtain attapulgite containing double bonds; a thiol-containing flame retardant and octadecyl mercaptan are compounded, and further thiol-ene click reaction occurs with the attapulgite containing double bonds, and the reaction process is environmentally friendly, which not only improves the flame retardant properties of the material, but also gives it excellent hydrophobic properties; further epoxy-terminated polydimethylsiloxane is introduced for compounding, and the molecular structure of epoxy-terminated polydimethylsiloxane contains siloxy chains and epoxy groups, which helps to improve the hydrophobic properties of the material, effectively improves the compatibility between the modified attapulgite and the epoxy resin, improves the adhesion and durability of the coating, and finally obtains a durable super hydrophobic protective layer. DETAILED DESCRIPTION
[0041] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] In this embodiment, attapulgite: particle size is 2000 mesh, sourced from Tuoyi New Materials (Guangzhou) Co., Ltd.; polypropylene: brand is Shanghai Petrochemical R700M; tinned copper wire conductor: diameter 0.5 mm, sourced from Shenzhen Hongguangsheng Technology Co., Ltd.; PP wax: brand is Clariant Licocene PP2502; compatibilizer: polypropylene grafted maleic anhydride, brand is Exxon PO1020 of the United States; end-epoxy polydimethylsiloxane: brand is 276-6K, sourced from Jiaxing United Chemical Co., Ltd.; shielding layer: copper tape, material T2, sourced from Shanghai Xingnuo Industrial Co., Ltd.; water-based epoxy resin: brand is Dow DER-916 of the United States.
[0043] In the following examples and comparative examples, 1 part is equal to 10 g.
[0044] Embodiment 1: A processing technology for an environmentally friendly water-blocking photovoltaic cable, comprising the following processes:
[0045] Step S1: 10 parts of modified attapulgite, 50 parts of polypropylene, 1 part of a compatibilizer, and 0.5 parts of PP wax are mixed evenly, and melt-extruded to obtain a water-blocking layer;
[0046] Step S2: 5 parts of modified attapulgite, 3 parts of epoxy-terminated polydimethylsiloxane, 40 parts of waterborne epoxy resin and 8 parts of curing agent are mixed evenly to obtain a protective coating;
[0047] Step S3: Wrapping the outer surface of the wire core (composed of 5 tinned copper wire conductors twisted together) with a water-blocking layer, a shielding layer, and a water-blocking layer in sequence, coating the surface of the water-blocking layer with a protective coating, and after curing, obtaining a protective layer sleeve, thereby obtaining an environmentally friendly water-blocking photovoltaic cable;
[0048] The preparation method of modified attapulgite is as follows:
[0049] Step (1): ultrasonically disperse 15 parts of attapulgite in a mixed solution of 20 parts of ammonia water and 80 parts of propylene glycol methyl ether, add 15 parts of ethyl orthosilicate, 5 parts of hexadecyltrimethoxysilane, and 8 parts of γ-methacryloxypropyltrimethoxysilane, react at 55° C. for 2 hours, and obtain attapulgite containing double bonds after filtering, washing, and drying;
[0050] Step (2): Under nitrogen protection, 10 parts of a thiol-containing flame retardant and 5 parts of octadecyl mercaptan were mixed to obtain a mixture; 15 parts of double-bond attapulgite, 15 parts of the mixture and 0.45 parts of a photoinitiator were mixed to obtain a mixture; after ultraviolet light irradiation (irradiation wavelength 360nm, irradiation time 0.5h, irradiation intensity 25mW / cm 2 ), to obtain modified attapulgite;
[0051] The preparation method of the mercapto-containing flame retardant is as follows:
[0052] Step A: 10 parts of 1,5-diaminonaphthalene, 14 parts of 3-aminopropyltriethoxysilane and 80 parts of ethanol were mixed evenly, and a mixed solution of 8 parts of terephthalaldehyde and 16 parts of ethanol was added, and the mixture was reacted at 60° C. for 4 hours to obtain an amino compound;
[0053] Step B: Under nitrogen protection, 5 parts of L-cysteine, 0.5 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 0.4 parts of 1-hydroxybenzotriazole were mixed evenly, reacted for 2 hours, 10 parts of a mixed solution containing an amino compound and 20 parts of DMF were added dropwise, and the mixture was added dropwise for 30 minutes. The mixture was reacted at 30° C. for 6 hours, and the intermediate was obtained after filtration, washing and drying.
[0054] Step C: Under nitrogen protection, 10 parts of the intermediate, 10 parts of DOPO and 80 parts of ethanol were mixed evenly, refluxed at 70° C. for 10 hours, cooled to room temperature, filtered, washed and dried to obtain a thiol-containing flame retardant.
[0055] Embodiment 2: A processing technology for an environmentally friendly water-blocking photovoltaic cable, comprising the following processes:
[0056] Step S1: 15 parts of modified attapulgite, 55 parts of polypropylene, 2 parts of a compatibilizer, and 0.8 parts of PP wax are mixed evenly, and melt-extruded to obtain a water-blocking layer;
[0057] Step S2: 8 parts of modified attapulgite, 5 parts of epoxy-terminated polydimethylsiloxane, 45 parts of waterborne epoxy resin and 10 parts of curing agent are mixed uniformly to obtain a protective coating;
[0058] Step S3: Wrapping the outer surface of the wire core (composed of 5 tinned copper wire conductors twisted together) with a water-blocking layer, a shielding layer, and a water-blocking layer in sequence, coating the surface of the water-blocking layer with a protective coating, and after curing, obtaining a protective layer sleeve, thereby obtaining an environmentally friendly water-blocking photovoltaic cable;
[0059] The preparation method of modified attapulgite is as follows:
[0060] Step (1): ultrasonically dispersing 23 parts of attapulgite in a mixed solution of 30 parts of ammonia water and 90 parts of propylene glycol methyl ether, adding 25 parts of ethyl orthosilicate, 8 parts of hexadecyltrimethoxysilane, and 10 parts of γ-methacryloxypropyltrimethoxysilane, reacting at 60° C. for 3 hours, filtering, washing, and drying to obtain attapulgite containing double bonds;
[0061] Step (2): Under nitrogen protection, 28 parts of a thiol-containing flame retardant and 18 parts of octadecyl mercaptan were mixed evenly to obtain a mixture; 23 parts of double-bond attapulgite, 46 parts of the mixture and 1 part of a photoinitiator were mixed evenly, and after ultraviolet light irradiation (irradiation wavelength 380nm, irradiation time 1h, irradiation intensity 30mW / cm 2 ), to obtain modified attapulgite;
[0062] The preparation method of the mercapto-containing flame retardant is as follows:
[0063] Step A: 28 parts of 1,5-diaminonaphthalene, 42 parts of 3-aminopropyltriethoxysilane and 250 parts of ethanol were mixed evenly, and a mixed solution of 24 parts of terephthalaldehyde and 72 parts of ethanol was added, and the mixture was reacted at 65° C. for 5 hours to obtain an amino compound;
[0064] Step B: Under nitrogen protection, 11.2 parts of L-cysteine, 1.68 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 1 part of 1-hydroxybenzotriazole were mixed evenly, reacted for 2.5 hours, 28 parts of a mixed solution containing an amino compound and 84 parts of DMF were added dropwise, and the mixture was added dropwise for 40 minutes. The mixture was reacted at 35° C. for 7 hours, and the intermediate was obtained after filtration, washing and drying.
[0065] Step C: Under nitrogen protection, 28 parts of the intermediate, 56 parts of DOPO and 250 parts of ethanol were mixed evenly, refluxed at 75° C. for 11 hours, cooled to room temperature, filtered, washed and dried to obtain a thiol-containing flame retardant.
[0066] Embodiment 3: A processing technology for an environmentally friendly water-blocking photovoltaic cable, comprising the following processes:
[0067] Step S1: 20 parts of modified attapulgite, 60 parts of polypropylene, 3 parts of a compatibilizer, and 1.0 part of PP wax are mixed evenly, and melt-extruded to obtain a water-blocking layer;
[0068] Step S2: 10 parts of modified attapulgite, 8 parts of epoxy-terminated polydimethylsiloxane, 50 parts of waterborne epoxy resin and 12 parts of curing agent are mixed uniformly to obtain a protective coating;
[0069] Step S3: Wrapping the outer surface of the wire core (composed of 5 tinned copper wire conductors twisted together) with a water-blocking layer, a shielding layer, and a water-blocking layer in sequence, coating the surface of the water-blocking layer with a protective coating, and after curing, obtaining a protective layer sleeve, thereby obtaining an environmentally friendly water-blocking photovoltaic cable;
[0070] The preparation method of modified attapulgite is as follows:
[0071] Step (1): ultrasonically disperse 25 parts of attapulgite in a mixed solution of 40 parts of ammonia water and 100 parts of propylene glycol methyl ether, add 30 parts of ethyl orthosilicate, 10 parts of hexadecyltrimethoxysilane, and 12 parts of γ-methacryloxypropyltrimethoxysilane, react at 65° C. for 4 hours, and obtain attapulgite containing double bonds after filtering, washing, and drying;
[0072] Step (2): Under nitrogen protection, 37.5 parts of a mercapto-containing flame retardant and 37.5 parts of octadecyl mercaptan were mixed evenly to obtain a mixture; 25 parts of double-bond attapulgite, 75 parts of the mixture and 2.5 parts of a photoinitiator were mixed evenly, and after ultraviolet light irradiation (irradiation wavelength 400nm, irradiation time 2.0h, irradiation intensity 35mW / cm 2 ), to obtain modified attapulgite;
[0073] The preparation method of the mercapto-containing flame retardant is as follows:
[0074] Step A: 40 parts of 1,5-diaminonaphthalene, 64 parts of 3-aminopropyltriethoxysilane and 400 parts of ethanol are mixed evenly, and a mixed solution of 36 parts of terephthalaldehyde and 144 parts of ethanol is added, and the mixture is reacted at 70° C. for 6 hours to obtain an amino compound;
[0075] Step B: Under nitrogen protection, 16 parts of L-cysteine, 3.2 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 1.6 parts of 1-hydroxybenzotriazole were mixed evenly, reacted for 3 hours, 40 parts of a mixed solution containing an amino compound and 160 parts of DMF were added dropwise, and the mixture was added for 50 minutes. The mixture was reacted at 40° C. for 8 hours, and the intermediate was obtained after filtration, washing and drying.
[0076] Step C: Under nitrogen protection, 40 parts of the intermediate, 120 parts of DOPO and 400 parts of ethanol were mixed evenly, refluxed at 80° C. for 12 hours, cooled to room temperature, filtered, washed and dried to obtain a thiol-containing flame retardant.
[0077] Comparative Example 1: A processing technology for an environmentally friendly water-blocking photovoltaic cable, comprising the following processes:
[0078] Step S1: 15 parts of attapulgite containing double bonds, 55 parts of polypropylene, 2 parts of a compatibilizer, and 0.8 parts of PP wax are mixed evenly, and melt-extruded to obtain a water-blocking layer;
[0079] Step S2: 8 parts of attapulgite containing double bonds, 5 parts of epoxy-terminated polydimethylsiloxane, 45 parts of waterborne epoxy resin and 10 parts of curing agent are mixed uniformly to obtain a protective coating;
[0080] Step S3: Wrapping the outer surface of the wire core (composed of 5 tinned copper wire conductors twisted together) with a water-blocking layer, a shielding layer, and a water-blocking layer in sequence, coating the surface of the water-blocking layer with a protective coating, and after curing, obtaining a protective layer sleeve, thereby obtaining an environmentally friendly water-blocking photovoltaic cable;
[0081] Compared with Example 2, in Comparative Example 1, the modified attapulgite is replaced with attapulgite containing double bonds of the same mass, and the other steps are the same as those in Example 2.
[0082] Comparative Example 2: A processing technology for an environmentally friendly water-blocking photovoltaic cable, comprising the following processes:
[0083] Step S1: 15 parts of modified attapulgite, 55 parts of polypropylene, 2 parts of a compatibilizer, and 0.8 parts of PP wax are mixed evenly, and melt-extruded to obtain a water-blocking layer;
[0084] Step S2: 8 parts of modified attapulgite, 45 parts of waterborne epoxy resin and 10 parts of curing agent are mixed evenly to obtain a protective coating;
[0085] Step S3: Wrapping the outer surface of the wire core (composed of 5 tinned copper wire conductors twisted together) with a water-blocking layer, a shielding layer, and a water-blocking layer in sequence, coating the surface of the water-blocking layer with a protective coating, and after curing, obtaining a protective layer sleeve, thereby obtaining an environmentally friendly water-blocking photovoltaic cable;
[0086] Compared with Example 2, no epoxy-terminated polydimethylsiloxane is added to the protective coating of Comparative Example 2, and other steps are the same as those of Example 2.
[0087] Comparative Example 3: A processing technology for an environmentally friendly water-blocking photovoltaic cable, comprising the following processes:
[0088] The preparation method of modified attapulgite is as follows:
[0089] Step (1): ultrasonically dispersing 23 parts of attapulgite in a mixed solution of 30 parts of ammonia water and 90 parts of propylene glycol methyl ether, adding 25 parts of ethyl orthosilicate, 8 parts of hexadecyltrimethoxysilane, and 10 parts of γ-methacryloxypropyltrimethoxysilane, reacting at 60° C. for 3 hours, filtering, washing, and drying to obtain attapulgite containing double bonds;
[0090] Step (2): Under nitrogen protection, 28 parts of DOPO and 18 parts of octadecyl mercaptan were mixed evenly to obtain a mixture; 23 parts of attapulgite containing double bonds, 46 parts of the mixture and 1 part of a photoinitiator were mixed evenly, and after ultraviolet light irradiation (irradiation wavelength 380nm, irradiation time 1h, irradiation intensity 30mW / cm2 ), to obtain modified attapulgite;
[0091] Compared with Example 2, in Comparative Example 3, the mercapto-containing flame retardant is replaced with DOPO of the same mass, and the other steps are the same as those of Example 2.
[0092] Experiment: Take the protective layer sleeves obtained in Examples 1-3 and Comparative Examples 1-3, prepare samples, test their properties respectively and record the test results:
[0093] Flame retardancy: refer to the flame retardancy level of the vertical burning test in GB / T2408-2008 for testing, and the sample size is 100mm long × 50mm wide; Hydrophobicity: use a contact angle tester to measure the water contact angle, and the test liquid is a 4μL water droplet; Tensile strength: refer to GB / T 1040.3-2006 "Test of Tensile Properties of Plastics" to determine the tensile strength, the sample size is 150mm×15mm×1mm, and the stretching speed is 25mm / min.
[0094] The test results are as follows:
[0095] Flame retardant grade Water contact angle / ° Tensile strength / MPa Example 1 V-0 148.4 37.2 Example 2 V-0 149.2 37.5 Example 3 V-0 147.5 36.8 Comparative Example 1 V-1 133.6 34.3 Comparative Example 2 V-0 138.7 36.1 Comparative Example 3 V-1 145.0 35.7
[0096] According to the data in the above table, we can clearly draw the following conclusions:
[0097] 1. Compared with Examples 1-3, the flame retardant grade, water contact angle and tensile strength of the product obtained in Comparative Example 1 are all decreased, indicating that compared with the double-bond attapulgite, the modified attapulgite prepared by the present invention has better flame retardant effect and hydrophobicity, and the introduction of a rigid structure effectively improves the flame retardant properties and mechanical properties of the material; the water contact angle of the product obtained in Comparative Example 2 is decreased, and it can be seen that the introduction of terminal epoxy polydimethylsiloxane in the present invention is helpful to improve the hydrophobicity of the material.
[0098] 2. Compared with Examples 1-3, the flame retardant grade and tensile strength of the product obtained in Comparative Example 3 are both reduced, which indicates that compared with DOPO of the same mass, the mercapto-containing flame retardant prepared by the present invention has better flame retardant properties and compatibility, and can better improve the mechanical properties of the material.
[0099] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A processing technology for an environmentally friendly water-blocking photovoltaic cable, characterized in that: The steps include: Step S1: uniformly mixing modified attapulgite, polypropylene, a compatibilizer, and a lubricant, and melt-extruding the mixture to obtain a water-blocking layer; Step S2: uniformly mixing the modified attapulgite, the epoxy-terminated polydimethylsiloxane, the waterborne epoxy resin and the curing agent to obtain a protective coating; Step S3: sequentially wrapping a water-blocking layer, a shielding layer, and a water-blocking layer on the outer surface of the wire core, coating the surface of the water-blocking layer with a protective coating, and after curing, obtaining a protective layer sleeve to prepare an environmentally friendly water-blocking photovoltaic cable.
2. The processing technology of an environmentally friendly water-blocking photovoltaic cable according to claim 1 is characterized in that: The water-blocking layer is composed of the following components in parts by weight: 50-60 parts of polypropylene, 10-20 parts of modified attapulgite, 1-3 parts of a volume extender, and 0.5-1.0 parts of a lubricant.
3. The processing technology of an environmentally friendly water-blocking photovoltaic cable according to claim 1 is characterized in that: The protective coating is composed of the following components in parts by weight: 5-10 parts of modified attapulgite, 3-8 parts of epoxy-terminated polydimethylsiloxane, 40-50 parts of waterborne epoxy resin, and 8-12 parts of curing agent.
4. The processing technology of an environmentally friendly water-blocking photovoltaic cable according to claim 1 is characterized in that: The preparation method of the modified attapulgite is as follows: Step (1): ultrasonically dispersing attapulgite in a mixed solution of ammonia water and propylene glycol methyl ether, adding ethyl orthosilicate, hexadecyltrimethoxysilane, and γ-methacryloxypropyltrimethoxysilane, reacting at 55-65° C. for 2-4 hours, filtering, washing, and drying to obtain attapulgite containing double bonds; Step (2): Under nitrogen protection, the mercapto-containing flame retardant and octadecyl mercaptan are mixed evenly to obtain a mixture; the double-bond attapulgite, the mixture and a photoinitiator are mixed evenly, and after irradiation with ultraviolet light, modified attapulgite is obtained.
5. The processing technology of an environmentally friendly water-blocking photovoltaic cable according to claim 4 is characterized in that: In the step (1), the double bond-containing attapulgite is composed of the following components in parts by weight: 15-25 parts of attapulgite, 20-40 parts of aqueous ammonia, 80-100 parts of propylene glycol methyl ether, 15-30 parts of tetraethyl orthosilicate, 5-10 parts of hexadecyltrimethoxysilane, and 8-12 parts of γ-methacryloxypropyltrimethoxysilane.
6. The processing technology of an environmentally friendly water-blocking photovoltaic cable according to claim 4 is characterized in that: The preparation method of the mercapto-containing flame retardant is as follows: Step A: 1,5-diaminonaphthalene, 3-aminopropyltriethoxysilane and ethanol are uniformly mixed, a mixed solution of terephthalaldehyde and ethanol is added, and the mixture is reacted at 60-70° C. for 4-6 hours to obtain an amino compound; Step B: Under nitrogen protection, L-cysteine, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 1-hydroxybenzotriazole are mixed evenly, reacted for 2-3 hours, a mixed solution containing an amino compound and DMF is added dropwise, and the mixture is added dropwise for 30-50 minutes, and the mixture is reacted at 30-40° C. for 6-8 hours. After filtering, washing and drying, an intermediate is obtained; Step C: Under nitrogen protection, the intermediate, DOPO and ethanol are mixed evenly, refluxed at 70-80° C. for 10-12 hours, cooled to room temperature, filtered, washed and dried to obtain a thiol-containing flame retardant.
7. The processing technology of an environmentally friendly water-blocking photovoltaic cable according to claim 6 is characterized in that: In the step C, the mass ratio of the intermediate, DOPO and ethanol is 1:(1-3):(8-10).
8. The processing technology of an environmentally friendly water-blocking photovoltaic cable according to claim 1 is characterized in that: The wire core is formed by twisting 3 to 6 tinned copper wire conductors.
9. The processing technology of an environmentally friendly water-blocking photovoltaic cable according to claim 1 is characterized in that: The shielding layer is a copper tape.
10. An environmentally friendly water-blocking photovoltaic cable manufactured according to the processing technology described in any one of claims 1 to 9.
Citation Information
Patent Citations
Solar energy photovoltaic cable and preparation method thereof
CN108359166A
Waterproof photovoltaic cable and processing technology thereof
CN117012469A
Cited By
Fireproof cable material and preparation method thereof
CN120623610A